Multiobjective Optimization Design of Green Building Energy Consumption Based on Inorganic Thermal Insulation Nanomaterials - Yuan Yuan; Songtao Li (International Journal of Analytical Chemistry)
In order to solve the problem that building engineering construction needs to consume a lot of energy and cause environmental pollution, which will pose a great pressure on urban resources and environment, this paper proposes that, in building engineering construction, appropriate green construction technology must be selected in combination with the actual situation, so as to effectively reduce the energy consumption of building engineering and improve the use efficiency of building engineering. Firstly, good thermal insulation nanomaterials are selected, which are cost-effective, safe, and nontoxic and has small thermal conductivity, large heat storage coefficient, stable chemical performance, and good construction performance. Secondly, it also needs to be selected according to the actual service life of the building. Because the current evaluation system is mostly aimed at the planning and design stage, and the structure occupies a large part in the building, for example, the impact on the construction period accounts for more than 50% and the impact on the cost accounts for 35%. Therefore, Duan Xiaorong and others established the grey cluster evaluation model of green building structure design based on the triangular whitening weight function. Finally, according to the relevant national regulations, this paper optimizes the design of green buildings based on the basic principles of energy conservation and emission reduction, high quality, and high efficiency.